Bacteriocin production by Lactobacillus plantarum AMA-K isolated from Amasi, a Zimbabwean fermented milk product and study of the adsorption of bacteriocin AMA-K TO Listeria sp. - Todorov, Svetoslav D. (Sociedade Brasileira de Microbiologia, 2008)
Bacteriocin AMA-K produced by Lactobacillus plantarum AMA-K inhibits the growth of Enterococcus spp., Escherichia coli, Klebsiella pneumoniae and Listeria spp. Growth of strain AMA-K in BHI, M17, soy milk and molasses was similar to growth in MRS. The effect of organic nitrogen sources, carbohydrates, glycerol, K(2)HPO(4) and KH(2)PO(4), MgSO(4), MnSO(4), tri-ammonium citrate, Tween 80, vitamins and initial pH on bacteriocin AMA-K was determined. The mode of action of bacteriocin AMA-K was studied. The effect of bacteriocin AMA-K to actively growing Listeria innocua LMG13568, L. ivanovii subsp. ivanovii ATCC19119 and L. monocytogenes ScottA was determined. Adsorption of bacteriocin AMA-K to target cells at different temperatures, pH and in presence of Tween 20, Tween 80, ascorbic acid, potassium sorbate, sodium nitrate and sodium chloride were studied. Bacteriocin AMA-K shares high homology to pediocin PA-1.